Methodology of management accounting in supporting management processes of marketing activities of agricultural enterprises in Ukraine - Vlasov , Volodymyr (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2025)
Management accounting in the marketing activities of Ukrainian agricultural enterprises is a key tool for effective decision-making under conditions of digital transformation, military disruption, and European integration. The study focuses on the adaptation of accounting systems to marketing needs, emphasizing cost analysis, profitability assessment, and integration with digital platforms such as CRM and ABC analysis.Problem statement. The main problem lies in the lack of standardized approaches to accounting for marketing expenses, insufficient integration with digital tools, and a shortage of qualified personnel. These issues hinder the formation of data-driven marketing strategies and reduce the effectiveness of management decisions.Unresolved aspects of the problem. Challenges include the limited structure of account 93 “Selling expenses,” absence of unified methodologies for calculating marketing costs, and underutilization of ROI and segment analysis tools. The impact of biological asset variability and seasonal cycles on accounting remains insufficiently studied.Purpose of the article. To analyze management accounting methods that support marketing processes in agricultural enterprises, and to propose practical recommendations for improving accounting systems in line with digital transformation and international standards.Presentation of the main material. The article classifies accounting models by cost recording method, analytical structure, and level of digital integration. It highlights the role of ABC analysis, ROI tracking, and cost/profit center accounting in evaluating marketing effectiveness. Successful practices in export-oriented enterprises and the berry sector are examined.Conclusions. Management accounting enhances marketing efficiency by enabling cost control, profitability analysis, and strategic planning. Its modernization is essential for improving competitiveness and sustainability in domestic and international markets.